Phoneme awareness is a better predictor of early reading skill than onset-rime awareness. - Hulme, C; Hatcher, P; Nation, K; Brown, A; Adams, J; Stuart, G (2002)
We present the results of a short-term longitudinal study. Children in the early stages of learning to read (5 and 6 year olds) were administered three different tasks (deletion, oddity, and detection) tapping awareness of four phonological units (initial phoneme, final phoneme, onset, and rime). Measures of phoneme awareness were the best concurrent and longitudinal predictors of reading skill with onset-rime skills making no additional predictive contribution once phonemic skills were accounted for. The findings are related to recent controversy over the role of large versus small phonological units as predictors of children's reading skills.